INVESTIGATION OF THE INJURY ANXIETY OF FEMALE ATHLETES ACCORDING TO VARIOUS VARIABLES - KAYHAN, Recep Fatih; YAPICI, Adem; ÜSTÜN, Ümit Doğan (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2019)
The aim of this study was to investigate the injury anxiety levels of female athletes according to various variables. 210 female athletes interested in various sports branches participated in the study. To collect data in addition to personal information form Turkish version of Rex and Metzler (2016)’ s “Sport Injury Anxiety Scale” was used. The Turkish version of the scale was adopted into Turkish culture by Caz, Kayhan and Bardakçı in 2019. The data was collected online via Google forms. In the evaluation of the data first, normality assumptions were checked. Than independent samples t test and one way ANOVA statistical methods were used in order to determine the significant differences. According to analyze results there were no significant differences in the variable sports injury anxiety according to age, education status, sports status and status of having a surgery before (p > .05). However, there were significant differences in the sub-dimension “losing potential” according to sport experience (p= .017) and, in the “loss of athletic ability” sub-dimension according to sports branch (p= .028).